Importance of the Psychosocial Care Network for the recovery of chemical dependents (Research, Society and Development, 2022)
Chemical dependency is a serious health problem, it is an incurable pathology that is characterized by its progressive character and that affects Brazilians in all different areas. Thus, taking into account the characterization of such pathology and the scarcity of studies about the effective role of the Psychosocial Care Network for the recovery of these patients, it is crucial to understand the impacts of this network. Objectives: To understand and analyze the role of Psychosocial Care Network in the recovery of chemical dependents. Methodology: This is an integrative review about the performance of RAPS in the recovery of chemical dependents. The PICO strategy was used to prepare the guiding question. In addition, the descriptors “Psychosocial Care Network” were crossed; “Chemical Dependency”; “Importance”; “Chemical Dependency” and “Drug Users” in the following databases: Virtual Health Library (VHL); Scientific Electronic Library Online (SCIELO) and PubMed. Results and Discussion: From the 11 selected studies, it is noted that the lack of a support network can directly interfere with the recovery and reintegration of chemical dependents. Conclusion: After this review, the importance of strengthening the Psychosocial Care Network and greater allocation of resources for its better performance is highlighted.